The Relationship Between Cybercrime and the Nigerian Economy: Causes, Implications and the Path Forward - Udoinyang , Nathan; Daniel, Reuben; David, Abroad (International Ecsis Association, 2024)
This study investigates the intricate relationship between cybercrime and Nigeria’s economic landscape, focusing on its causes, implications, and potential mitigation pathways. Cybercrime has evolved into a systemic challenge in Nigeria, fueled by socio-economic disparities, institutional weaknesses, and behavioural tendencies, threatening financial stability and economic development. The primary objective of this research is to identify the dominant drivers of cybercrime and assess its economic consequences, with the goal of proposing collaborative strategies for mitigation. A survey-based quantitative approach was employed, targeting five major Nigerian banks—Access Bank, First Bank, GT Bank, UBA, and Zenith Bank—and academic institutions, including the University of Port Harcourt and Ignatius Ajuru University of Education. A structured questionnaire (C.N.E.C.I.P.F.) was administered to a randomly selected sample of 300 individuals, of which 260 valid responses (86.7%) were analyzed using descriptive statistics and percentage analysis, with a 50% aggregate agreement threshold. Findings reveal that unemployment, poor law enforcement, urbanization, and corruption are primary contributors to cybercrime. The economic implications include loss of revenue, business disruption, and decreased investor confidence. While cybercrime cannot be fully eradicated, the study emphasizes the potential for reduction through synergistic collaboration between government, businesses, and citizens. This research contributes to the growing body of literature on cybercrime by offering empirical insights specific to the Nigerian context and proposes an inclusive, multistakeholder framework for mitigating its socio-economic effects.